Exploring the Benefits of Interactive Apps in Bilingual Physical Education: A Quantitative Analysis - Utami, Hadi Riwayati; Sumardiyani, Listyaning; Zahraini, Dian Ayu; Ambarini, Ririn (Journal of English Education, Literature and Linguistics, 2024)
The integration of interactive applications in bilingual physical education has emerged as a promising approach to enhance learning outcomes. This study aims to explore the benefits of using interactive apps in bilingual physical education settings. The research employs a quantitative methodology, involving the collection and analysis of data from students and teachers who use these applications. Surveys and standardized tests were administered to measure the impact on student engagement, knowledge retention, and overall physical performance. The findings reveal that interactive apps significantly improve student engagement and motivation, leading to better performance in physical activities and a deeper understanding of bilingual instructions. Additionally, teachers reported an increased ability to deliver complex concepts effectively and manage diverse classroom dynamics. These results suggest that interactive apps are a valuable tool in bilingual physical education, promoting both language acquisition and physical fitness. Future research should focus on long-term impacts and explore the integration of such technology in different educational contexts.